TRIZ and Pugh method analysis towards Conceptualizing a novel modular airless tyre - Subramonian, Sivarao; Karunamurthi, Lavanyaa; Lee, Sara Kit Yee; Kadirgama, Kumaran; Arep @ Ariff, Hambali; Rao, Dharsyanth; Salleh, Mohd Shukor; Ramasamy, Devarajan (Praise Worthy Prize, 2024)
Airless tyres are being developed in response to a growing need for safer tyres to address issues with pneumatic tyres. The constrained interaction between the spoke, hub, and outer ring has been identified as the cause of the lack of adjustability of airless tyres. Its complex interacted design makes the ‘one-piece’ airless tyre relatively expensive and extremely difficult to repair when damaged. This research focuses on developing a simpler version of a modular airless tyre that is cost-effective and easier to maintain for low-speed, heavy-duty drive applications, including off-road use for military vehicles and other purposes. The primary objectives were to identify and analyse the interactions of the airless tyre system’s core components, generate the concept of modular airless tyre employing Theory of Inventive Problem Solving (TRIZ) methodology and determine the final concept using Pugh method. Integrated functional analysis was performed to identify and analyse the interactions of airless tyre components. The solutions were generated using thirty-nine engineering parameters and a matrix of contradictions consisting of forty TRIZ principles of inventiveness. These inventive principle solutions were then refined into a specific solution strategy used to construct the modular airless tyre concept. As a result, four new innovative concepts for a modular airless tyre were generated based on the TRIZ principles #1 Segmentation, #6 Universality, #28 Replace Mechanical System, and #34 Rejecting and Regenerating Parts. Finally, the Pugh method was used to evaluate and determine the final concept of a modular airless tyre suitable for low-speed, heavy-duty drive applications.